Brain Fatigue is a Critical Issue - Habibzadeh Nasim; Wood Daniel (International Physiology Journal, 2019)
The brain is one of the most complicated body segments which processes almost all activities in human body. Excessive physical and mental overloads can cause brain fatigue and may put the brain health at risk of various disorders. Strategies such as reducing the workloads and performing mediation and walking provide opportunities for brain to relax and reconstruct its capability again.
Keywords: Brain functions